2019
DOI: 10.1111/jcpp.13114
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven identification of subtypes of executive function across typical development, attention deficit hyperactivity disorder, and autism spectrum disorders

Abstract: Background Impairment of executive function (EF), the goal‐directed regulation of thoughts, actions, and emotions, drives negative outcomes and is common across neurodevelopmental disorders including attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). A primary challenge to its amelioration is heterogeneity in symptom expression within and across disorders. Parsing this heterogeneity is necessary to attain diagnostic precision, a goal of the NIMH Research Domain Criteria Initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 51 publications
(54 reference statements)
3
42
0
1
Order By: Relevance
“…Data-driven techniques are now being used to identify key dimensions of functioning that overlap across diagnostic categories and also present heterogeneously within diagnostic categories 81 . For example, transdiagnostic executive function subtypes have been identified with use of community detection algorithms, and children within the subtype characterized by inflexibility showed a failure to modulate parietal lobe activation in response to increasing executive task demands 82 . Other work examining ASD, ADHD and co-morbid ASD and ADHD using latent profile analysis also provides evidence for transdiagnostic executive function classes 65 .…”
Section: Flexibility In Clinical Conditionsmentioning
confidence: 99%
“…Data-driven techniques are now being used to identify key dimensions of functioning that overlap across diagnostic categories and also present heterogeneously within diagnostic categories 81 . For example, transdiagnostic executive function subtypes have been identified with use of community detection algorithms, and children within the subtype characterized by inflexibility showed a failure to modulate parietal lobe activation in response to increasing executive task demands 82 . Other work examining ASD, ADHD and co-morbid ASD and ADHD using latent profile analysis also provides evidence for transdiagnostic executive function classes 65 .…”
Section: Flexibility In Clinical Conditionsmentioning
confidence: 99%
“…Although the neuropsychological profile of ADHD is heterogeneous, numerous studies indicate that it involves impairments in various executive function (EF) domains (Barkley et al, 1992 ; Pennington and Ozonoff, 1996 ; Sergeant et al, 2002 ). Reported findings are hardly conclusive, however, since the mean effect sizes range from small to moderate for EF measures, and not all children with ADHD show EF deficits (Willcutt et al, 2005 ), which can also be seen in typically-developing (TD) children (Vaidya et al, 2020 ), suggesting that none of these EF deficits is a necessary or sufficient explanation for the ADHD profile (Willcutt et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the experience of short-term VSWM in ASD showed that the reducing efficiency of process was associated with the deficit of planning [30]. Importantly, ASD and ADHD may have overlap but distinct characteristics in the domain of EF [31,32]. Moreover, varying subtypes of EF could contribute to distinguish and better understand the cognitive characteristics [12,33].…”
Section: Introductionmentioning
confidence: 99%